2022
DOI: 10.21037/apm-22-563
|View full text |Cite
|
Sign up to set email alerts
|

Present situation and analysis of factors affecting perimenopausal syndrome among clinical nurses—a cross-sectional survey

Abstract: Background: The quality of life of women is seriously affected by perimenopausal symptoms and related diseases. Clinical nurses often suffer from job burnout due to high pressure and intensity of work and life, which is easy to induce and aggravate perimenopausal syndrome. Nursing occupational environment varies greatly in different economic regions, but relevant studies are limited to northern cities, and are often confined to the second and third grade hospitals or a hospital in a certain region, lacking mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Menopausal symptoms are unique abnormal symptoms in women and important factors affecting women’s physical and mental health and living standards. We found that the incidence of menopausal-related symptoms in women who underwent physical examinations was high, but to a lesser extent; this was basically consistent with the results of Ding et al [ 20 ] study carried out in nurses but slightly lower than the results of Huang et al [ 18 ] survey carried out in menopausal clinics in Shanghai, which may be related to different cultural backgrounds, economic levels, and populations selected for the survey. The occurrence of menopausal symptoms differs in women in different regions: surveys in Cambodia have found that the most prevalent menopausal symptom is fatigue [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…Menopausal symptoms are unique abnormal symptoms in women and important factors affecting women’s physical and mental health and living standards. We found that the incidence of menopausal-related symptoms in women who underwent physical examinations was high, but to a lesser extent; this was basically consistent with the results of Ding et al [ 20 ] study carried out in nurses but slightly lower than the results of Huang et al [ 18 ] survey carried out in menopausal clinics in Shanghai, which may be related to different cultural backgrounds, economic levels, and populations selected for the survey. The occurrence of menopausal symptoms differs in women in different regions: surveys in Cambodia have found that the most prevalent menopausal symptom is fatigue [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…So, nurses with high work seniority are also older. Some scholars (Ding et al, 2022 ; Kurniawan et al, 2019 ) have pointed out that with the increase of age, various skill levels, especially those related to strength, speed, coordination and agility, will continue to decline over time, so psychiatric nurses with high work seniority are more prone to fatigue. At the same time, psychiatric nurses with high work seniority face the physical and mental pain of patients with mental disorders all year round in clinical work and maintain relatively high mental tension for a long time (Gunawan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%